Aplicación de 'MY CLASS GAME' como estrategia de gamificación en la enseñanza de nomenclatura química inorgánica para estudiantes de nivelación en la modalidad virtual de la Universidad Nacional de Chimborazo. - Robalino Salas, Diego Israel (2024)
The study problem focuses on the lack of motivation of remedial students in learning Inorganic Chemistry nomenclature. To address this problem, the digital tool My Class Game was implemented, with the purpose of applying gamification in the teaching of this subject in the virtual modality of the National University of Chimborazo. We worked with two groups, with a total population of 1692 students, 43 students from parallel H (experimental group) and 34 students from parallel J (control group). The sample was obtained by convenience, since both groups do not exceed 50 students, with a quasi-experimental design because the hypothesis about the relationship between the variables was evaluated, the development of the game included the creation of interactive materials and a bank of 108 inorganic chemical compounds. These compounds were divided into binary, ternary, and quaternary, and included guidelines on their structures. The design also included recreational and academic penalties, which were based on visual participation and the presentation of academic work. The results of the study showed a significant difference between the groups. Therefore, My Class Game has had a positive impact on the academic performance of students, significantly improving their learning of Inorganic Chemistry nomenclature.